Neuropsychological impairment in soccer athletes - Downs, D. S.; Abwender, D. (The Journal of Sports Medicine and Physical Fitness, 2002)
BACKGROUND: Soccer reportedly places participants at risk for neuropsychological impairment, although it is unknown if the risk is associated primarily with concussion, subconcussive blows from heading the ball, or some combination thereof. Moreover, the extent to which younger versus older athletes are at risk for soccer-related cognitive impairment is unclear. We hypothesized that soccer athletes, especially older ones, would show poorer neuropsychological test performance than comparable swimmers. METHODS: Thirty-two soccer (26 college and 6 professional) and 29 swimmers (22 college and 7 masters level), all involved for at least 4 years in their sport at collegiate or national levels, participated. In a 2 X 2 (sport X age category) factorial design, all participants underwent 4 neuropsychological tests with 11 outcome measures assessing motor speed, attention, concentration, reaction time, and conceptual thinking. RESULTS: Soccer athletes performed worse than swimmers on measures of conceptual thinking. The older soccer group in particular performed poorly on measures of conceptual thinking, reaction time, and concentration. Among non-goaltender soccer athletes, estimates of career exposure to brain trauma (based on length of career and level of play) predicted significantly poorer test performance on 6 of 11 measures, even after statistically controlling for age. CONCLUSIONS: Results provide additional evidence that participation in soccer may be associated with poorer neuropsychological performance, although the observed pattern of findings does not specifically implicate heading as the cause. Although deficits were most apparent among older soccer players, serial neuropsychological testing for early detection of impairment is recommended for younger players as well.